Identification of Veratrum Species in Pimacao Based on ITS2 Sequences and Steroidal Alkaloids by a Pseudo-Targeted Metabolomics Method - Lu, Qinwei; Wang, Shuaiyao; Yin, Zili; Chen, Qinsheng; He, Xingchao; Wang, Qi; Hu, Qingyu; Gu, Yu; Tang, Huiru; Xie, Hui (Frontiers in Plant Science, 2022)
Pimacao is a traditional Chinese folk medicine and is the main component of the famous Chinese herbal remedy “Yunnan Baiyao” for its significant analgesic activity in the treatment of wounds. Due to increases in consumption, its wild population is now difficult to find, and adulterant from the same genus have been occurs. However, this is challenging for distinguish the species of Veratrum in Pimacao using dried roots and rhizomes or medicinal powder. ITS2 sequences and steroidal alkaloids by non-targeted and pseudo-targeted method were took advantage of establish an effective identification method. Based on the ITS2 sequence, metabolite profiling of steroidal alkaloids and morphological characteristics, the classification of two distinct subspecies in V. mengzeanum has been reinforced. In addition, the new subspecies V. mengzeanum subsp. phuwae was collected in China for the first time. The ITS2 sequence could be used in the identification of V. taliense, V. mengtzeanum, V. stenophyllum and V. nigrum, but is insufficient for intraspecific identification. Simultaneously, 147 variables were labelled by non-targeted analysis accomplished utilizing an ultra-high-performance liquid chromatography electrospray ionization orbitrap tandem mass spectrometry (UPLC-ESI-QE-Orbitrap-MS) system consisting of an Orbitrap QE HF-X. Followed by a pseudo-targeted analysis method developed for the Qtrap 6500-plus mass spectrometry system coupled with an ESI source, twenty-nine labelled steroidal alkaloids detected by the MRM mode could distinguish between four species. Notably, 25 labelled steroidal alkaloids could distinguish between three closely related species. These have the potential to be used as markers for identification. Furthermore, there were several variables with statistical differences between two subspecies of V. mengtzeanum and populations of V. taliense, V. mengtzeanum and V. stenophyllum.